SUNDANESE PAMALI VALUES AS A FONDATION FOR CHARACTER EDUCATION IN ELEMENTARY SCHOOL - widiastuti, hesti; Sinta Maria Dewi, Harmawati; Imas Indah Mutiara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Pamali is a form of belief that exists in society related to customs and manners. Pamali or commonly referred to as a prohibition or taboo that should not be violated because it is considered to have a bad impact on the perpetrator. Not only in the form of actions or behaviors that are considered not allowed, but also the use of certain sentences or language that are considered inappropriate or worth hearing. Sundanese society, especially in this study, the Karawang Regency community has its own view of pamali, a lot of pamali believed by the Sundanese community which is still a cultural heritage and is used today. The purpose of this study is to determine the educational value contained in the Pamali tradition of the Sundanese community as well as the character value contained in the Pamali tradition that is still alive in the Sundanese community today. The type of research used in this study is descriptive qualitative research with an ethnographic approach. Data obtained through direct observation and interviews with informants who know and understand the pamali tradition. As for the results of this study, that the character values contained in the pamali tradition consist of politeness values, manners values, and mutual respect values while the content of educational values consists of moral values and social values.